Use of etoricoxib in patients with gout in real clinical practice - M S Eliseyev; Viktoria Georgiyevna Barskova (Современная ревматология, 2013)
Objective: to evaluate the efficacy and safety of etoricoxib (Arcoxia ®) in gouty patients with an acute arthritis attack in real clinical practice. Subjects and methods. Thirty patients (25 men and 5 women; mean age 52.4±13.5 years) with crystal-verified gout participated in the pilot open-label study of the patients with arthritis, including those who had taken other nonsteroidal anti-inflammatory drugs (NSAIDs) without any effect. All the patients received etoricoxib (Arcoxia ®) in a dose of 120 mg/day for 7 days and, if arthritis persisted, in a dose of 90 mg/day for 7 more days. The authors estimated an articular index, swelling and hyperemia indices, resting and movement pain by a visual analogue scale (VAS), therapy tolerance in the patient's opinion before and 7 days after therapy and, in the patients taking etoricoxib for 14 days, after 14 days of therapy. Biochemical and clinical blood tests were carried out at the first and subsequent visits. Results. Seven days after therapy, an arthritis attack was abolished in 24 of the 28 patients, following 14 days, arthritis persisted only in 1 patient, but the number of affected joints reduced from 8 to 2. Following 7 days, there was a reduction in the mean erythrocyte sedimentation rate from 37.2+10.2 (before etoricoxib intake) to 15.3±8.3 mm/h (p<0.001), VAS resting pain from 48.6±21.4 to 5.2±3.5 mm (p<0.001), swelling (p<0.001) and hyperemia (p< 0.001) indices, and articular index (p<0.001). In 2 patients with baseline uncontrolled arterial hypertension, the drug was discontinued because of elevated blood pressure; periorbital edema was noted in one case by the end of a therapy course. There were no increases in the serum levels of liver enzymes, in the concentrations of creatinine and urea, and in glomerular filtration rate. Conclusion. Etoricoxib (Arcoxia ®) is highly effective and safe when used in patients with acute gouty arthritis, including those who had not benefited from previous NSAID therapy and those with oligoand polyarthritis.